PERANCANGAN STRUKTUR BETON BERTULANG GEDUNG KAMPUS II POLITEKNIK NEGERI PONTIANAK 8 LANTAI TAHAN GEMPA DI KOTA PONTIANAK: PERANCANGAN STRUKTUR BETON BERTULANG GEDUNG KAMPUS II POLITEKNIK NEGERI PONTIANAK 8 LANTAI TAHAN GEMPA DI KOTA PONTIANAK - Ismiatul Laila, Nur; rosanti, indah; rasiwan, rasiwan (RETENSI, 2022)
The rapid development in the field of education in order to obtain a superior successor of the nation sothat progress and increase in welfare are realized for all Indonesian people. As the population increases, so doesthe need for educational facilities. The improvement of higher education facilities and infrastructure is needed tofacilitate the teaching and learning process. The development carried out certainly needs to pay attention toseveral aspects, one of which is the effect of the earthquake. Earthquakes always attack the joint structure so thatthe structure is designed with the moment-bearing frame system method with the concept of strong columns andweak beams combined with shear walls so that the building can dampen earthquake vibrations.The 8-storey earthquake-resistant Pontianak State Polytechnic campus II building is located on JalanJenderal Ahmad Yani, Pontianak City, West Kalimantan Province. The building consists of 8 floors with a heightof 30.7 meters from the ground, reinforced concrete structure. Based on the results of the Standard PenetrationTest (SPT) this building will be erected on soft soil conditions (SE site class), included in the Seismic DesignCategory (KDS) D, then the calculation of this building uses the Special Moment Resistant Frame System(SRPMK) combined with walls shear so it is called the Dual System Method. Earthquake load planning uses the2017 Indonesia Earthquake Map using the response spectrum method according to SNI 1726-2019. Calculationof loading according to SNI 1727-2020 and PPPURG1987, and structural concrete requirements for buildingsaccording to SNI 2847-2019. Structural analysis using SAP2000 application assistanceThe results of the calculation of the floor slab obtained 1 type of plate measuring 14 cm with 10 mmreinforcement for the ground floor to 7th floor, 9 mm reinforcement for non-floor floors; the dimensions of themain beam structure are 20 × 40 cm with D19 main reinforcement, the dimensions of the sub-beam structure are20 × 40 cm with D16 main reinforcement; column dimensions 80 × 80 cm with 16D25 main reinforcement, liftcolumn dimensions 30 × 30 cm with 12D16 main reinforcement; 1 type of sliding wall 15 cm; ladder plate 12 cm;pile foundation 30 cm.